2020
DOI: 10.1007/s40820-020-00470-w
|View full text |Cite
|
Sign up to set email alerts
|

Conductive MOFs with Photophysical Properties: Applications and Thin-Film Fabrication

Abstract: HIGHLIGHTS • An overview on photophysical properties of conductive metal-organic frameworks (MOFs) including photoconductivity and photoluminescence is provided. • Miscellaneous applications of MOFs with photophysical properties are discussed. • Recent advances in integration of photoactive MOFs with practical devices are summarized. ABSTRACT Metal-organic frameworks (MOFs) are a class of hybrid materials with many promising applications. In recent years, lots of investigations have been oriented toward applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 117 publications
1
53
0
1
Order By: Relevance
“…Metal organic frameworks (MOFs) are a class of materials, whose crystalline is in framework structure constructed by connecting metal center with organic linker [13][14][15][16]. Such structure offers ultrahigh specific surface areas, regular and tunable pores, and open metal sites to molecules, rendering MOFs very attractive for improving gas sensing performance [17][18][19][20][21][22]. Campbell et al have reported that conductive 2D MOFs can be utilized as active materials for detecting volatile organic compounds (VOCs) and a sensor array based on MOFs with well-designed structure is able to discriminate different VOCs [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal organic frameworks (MOFs) are a class of materials, whose crystalline is in framework structure constructed by connecting metal center with organic linker [13][14][15][16]. Such structure offers ultrahigh specific surface areas, regular and tunable pores, and open metal sites to molecules, rendering MOFs very attractive for improving gas sensing performance [17][18][19][20][21][22]. Campbell et al have reported that conductive 2D MOFs can be utilized as active materials for detecting volatile organic compounds (VOCs) and a sensor array based on MOFs with well-designed structure is able to discriminate different VOCs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al have deposited ZIF-CoZn (an analogue of ZIF-8) on ZnO nanowire array to fabricate a sensor showing better performance to acetone with interference of humidity [19]. Additionally, a Janus nanostructure of Au@ ZnO@ ZIF-8 has been prepared and shows fast response to formaldehyde at room temperature [20]. Li et al have prepared various kinds of MOFs which show outstanding gas performance to formic acid as well as ammonia and ammines [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…33,34 The use of nanostructured heterogeneous catalysts in organic transformations has recently been very exciting owing to their catalytic efficiency and selectivity. [35][36][37][38][39][40] Furthermore, 2D materials have become an important platform to design numerous single-atom catalysts for diverse chemical reactions, such as N 2 reduction, CO 2 reduction, and CO oxidation. [41][42][43][44][45][46][47][48][49][50][51][52] The ease of isolation and separation of the heterogeneous catalysts from the desired organic product and the recyclability and reusability further enhanced the sustainability of the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] With light irradiation, LMCT in MOFs can emerge because of the transfer of energy with the HOMO‐LUMO gap related closely to the band gap. [ 23,24 ] Fabrication inorganic semiconductors with MOFs have been proved to be a significant method to improve the charge carrier separation with at least three profitable factors: first, more paths for the photo‐induced electrons migration can be taken place with more semiconductors involved [ 25–27 ] ; second, high surface area of MOFs will lead to the enlargement of adsorption capacities to POPs; finally, photoactive particles of inorganic semiconductors can be well dispersed on MOFs, impacting the exposure between POPs and active sites.…”
Section: Introductionmentioning
confidence: 99%